Alkali soluble resin, composition and use thereof
By adding alkali-soluble resin with an annular structure to the ink composition of the 5G communication circuit board, the dielectric constant and dielectric loss of the cured film are reduced, and the problem of insufficient performance of printed circuit boards and protective coatings in the 5G communication system is solved, and the effect of high transmission efficiency is achieved.
Patent Information
- Application Number
- CN202211283506.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-19
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-10-19
AI Technical Summary
The printed circuit boards used in 5G mobile communication systems and protective coatings coated on substrates need to have low loss and high transmission efficiency properties, and the resin needs to retain alkaline-soluble development and resolution capabilities.
By adding an alkali soluble resin with an annular structure to the ink composition, the dielectric constant and dielectric loss of the cured film are reduced, thereby improving the transmission rate.
The photosensitive resin composition used on the 5G communication circuit board is realized, with low dielectric constant and dielectric loss, and the transmission efficiency of the communication line is improved.
Smart Images

Figure BDA0003897809400000041 
Figure BDA0003897809400000042 
Figure BDA0003897809400000043
Abstract
Description
Technical Field
[0001] The present invention relates to an alkali-soluble resin. More specifically, the present invention relates to an alkali-soluble photosensitive resin composition with low dielectric constant and low dielectric loss, and its use in a photosensitive solder resist ink on a communication board of a 5th generation (5G) mobile communication system. Background Art
[0002] 5G mobile communication technology has a high-quality communication experience and is in line with future development. Compared with traditional 4G technology, 5G communication technology not only has higher and faster transmission speed and higher transmission efficiency, but also has the advantages of shorter network delay, excellent scalability and interactivity. In short, the future 5G technology can greatly change the existing communication methods and improve the comprehensive level of communication technology to meet the needs of people in the future.
[0003] Therefore, the printed circuit board (PCB) used in the 5G communication field is required to have low loss and high transmission efficiency, and the protective coating applied on the 5G communication PCB substrate is also required to have low loss and high transmission efficiency. The high frequency and high speed development characteristics of 5G communication have reshaped the entire PCB industry and also brought new development directions to PCB inks.
[0004] Therefore, it is particularly necessary to provide a cured coating for 5G communication circuit boards, which not only has the stability of ordinary circuit board cured films, but also has a lower dielectric constant (Dielectric constant, D k ) and dielectric loss (Dissipation factor, D f ), while retaining the alkali-soluble development and resolution capabilities of the resin. Summary of the invention
[0005] In order to solve the above problems, the inventors surprisingly found that by adding an alkali-soluble resin having a cyclic structure into the ink composition, the dielectric constant and dielectric loss of the cured film can be reduced, thereby reducing the loss performance of the ink of the present invention and improving the transmission rate.
[0006] In one aspect, the present invention provides an alkali-soluble resin having a cyclic structure, wherein the alkali-soluble resin having a cyclic structure is one or a combination of resins a, b and c selected from the following:
[0007] Resin a. is a copolymer obtained by copolymerizing an unsaturated monobasic acid (B-1), a polymerizable monomer containing a cyclic structure (B-2) and an alkyl (meth)acrylate monomer (B-3) under a free radical initiation system, wherein the alkyl group in the monomer (B-3) is a chain alkyl group having 4 to 20 carbon atoms;
[0008] Resin b is a resin obtained by reacting the resin a and an unsaturated polymerizable monomer having an epoxy group (B-4);
[0009] Resin c. is a resin obtained by reacting the resin a and an unsaturated epoxy monomer (B-5) having an alicyclic skeleton.
[0010] In another aspect, the present invention provides a photosensitive resin composition comprising:
[0011] (A) an alkali-soluble photocurable resin, in an amount of 40 to 80% by weight, preferably 50 to 70% by weight, based on the total weight of component (A) and component (B);
[0012] (B) an alkali-soluble resin containing a cyclic skeleton structure, which is different from component (A) and is present in an amount of 20 to 60% by weight, preferably 30 to 50% by weight, based on the total weight of component (A) and component (B);
[0013] (C) a photopolymerization initiator, in an amount of 0.3-10 parts by weight, preferably 0.9-8 parts by weight;
[0014] (D) a photosensitive monomer, in an amount of 1-40 parts by weight, preferably 8-30 parts by weight;
[0015] (E) a solvent-type diluent, in an amount of 5-200 parts by weight, preferably 5-100 parts by weight;
[0016] (F) pigments and fillers and other additives other than pigments and fillers, the content of which is 30-240 parts by weight, preferably 60-150 parts by weight;
[0017] (G) a thermosetting component, in an amount of 0.6-25 parts by weight, preferably 50-20 parts by weight;
[0018] The amounts of components (B) to (G) are all based on 100 parts by weight of the total weight of components A and B in the photosensitive resin composition.
[0019] Another aspect of the present invention provides a circuit board comprising a cured coating formed from the photosensitive resin composition of the present invention.
[0020] The resin composition of the present invention has an appropriate amount of carboxyl groups, double bonds and photosensitive monomers, as well as a characteristic alicyclic skeleton structure, so that it can fully meet the various performance requirements of 5G communication inks and can completely solve the dielectric constant and dielectric loss problems of circuit boards.
[0021] The present invention can provide a high-performance photosensitive resin composition for 5G communication circuit boards. The photosensitive resin composition has the excellent developability of ordinary resin compositions, can participate in ink curing film formation, and provides excellent hardness, heat resistance, chemical resistance and other properties. The most important characteristic performance is that the polymerized monomer containing an alicyclic skeleton structure used for polymerization can provide a lower dielectric constant and dielectric loss, so the D of the ink used for 5G communication can be greatly reduced. k and D f , which effectively improves the transmission efficiency of communication lines, and therefore has extremely high practical value in the field of 5G communications. DETAILED DESCRIPTION
[0022] In the present invention, unless otherwise stated, all operations are carried out at room temperature (25° C.) and normal pressure (101 KPa); unless otherwise stated, the contents of the present invention are expressed in weight fraction (wt %).
[0023] In the present invention, the acid value refers to the value obtained by the acid-base titration method with the aid of a KOH standard solution according to GB / T2895-2008. The viscosity is measured according to the test method for unsaturated polyester resins in GB / T 7193-2008. The weight average molecular weight is measured by gel permeation chromatography (GPC) according to GB / T21863-2008 using tetrahydrofuran (THF) as an elution solvent and polystyrene as a standard curve. The solid content is measured according to the test method for unsaturated polyester resins in GB / T 7193-2008.
[0024] In the present invention, unless otherwise specified, the term "resin" is used synonymously with "solid content of resin". This is because in use, "resin" usually contains a solvent component (for example, to reduce viscosity and facilitate operation), however, when it comes to calculating material ratios, determining acid values, etc., usually only the components without solvent are considered, which is well known to those skilled in the art.
[0025] The present invention provides an alkali-soluble resin having a cyclic structure (hereinafter also referred to as "alkali-soluble resin (B)"), wherein the alkali-soluble resin is a resin selected from the following or a combination thereof:
[0026] Resin a. is a copolymer obtained by copolymerizing an unsaturated monobasic acid (B-1), a polymerizable monomer containing a cyclic structure (B-2) and an alkyl (meth)acrylate monomer (B-3) under a free radical initiation system, wherein the alkyl group in the monomer (B-3) is a chain alkyl group having 4 to 20 carbon atoms;
[0027] Resin b is a resin obtained by reacting the resin a and an unsaturated polymerizable monomer having an epoxy group (B-4);
[0028] Resin c. is a resin obtained by reacting the resin a and an unsaturated epoxy monomer (B-5) having an alicyclic skeleton.
[0029] In the present invention, the copolymeric alkali-soluble resin (B) containing an alicyclic skeleton structure can be obtained by one of the following methods i, ii and iii or a combination thereof:
[0030] i. Resin a (i.e., product a) is obtained by copolymerizing unsaturated monoacid (meth) acrylic acid (B-1), a polymerizable monomer containing an alicyclic skeleton (B-2), and a (meth) acrylic acid alkyl ester monomer containing 4 to 20 carbon chains in the molecule (B-3) under a free radical initiation system, wherein the solid content acid value of resin a is 60 to 320 mgKOH / g and the weight average molecular weight is 2000 to 50000;
[0031] In the present invention, product a is shown in the following formula 1
[0032]
[0033] Among them, the unsaturated monobasic acid (B-1) is not limited to methacrylic acid (such as acrylic acid), and R in B-2 1 is an alkyl group containing an alicyclic skeleton, and R in B-3 2 It is an alkyl group with a carbon chain of 4 to 20.
[0034] ii. reacting the product a obtained in method i with an unsaturated polymerizable monomer (B-4) having an epoxy group to obtain a resin b (ie, product b), wherein the solid content acid value of the resin b is 30-300 mgKOH / g and the weight average molecular weight is 8,000-80,000;
[0035] In one embodiment of the present invention, product b is shown in Formula 2
[0036]
[0037] Among them, B-4 is not limited to glycidyl methacrylate, but should also include similar unsaturated epoxy monomers and prepolymers thereof.
[0038] iii. reacting the product a obtained in method i with an unsaturated epoxy monomer having an alicyclic skeleton (B-5) to obtain a resin c (ie, product c), wherein the solid content acid value of the resin c is 100-400 mgKOH / g and the weight average molecular weight is 10,000-80,000;
[0039] Product c is shown in Formula 3
[0040]
[0041] In the above formula (3), R in the structure B-5 is 3 It is an H atom or an alkyl group with no more than 4 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, but not limited thereto; it may also include other groups, such as: 1,2-epoxy-3-vinylcyclohexane, 1,2-epoxy-4-vinylcyclohexane, 1,2-epoxy-4-isopropenylcyclohexane, 1,2-epoxy-4-propenylcyclohexane, 1,2-epoxy-(3,3)-divinylcyclohexane, cyclopentadiene epoxide, etc.
[0042] The relationship between the above resins a, b, and c is that a is not photosensitive but is alkali soluble. b and c are resins obtained by copolymerizing the resin a and then esterifying the side chain carboxyl groups with an unsaturated polymer monomer (B-4) having an epoxy group or an unsaturated epoxy monomer (B-5) having an alicyclic skeleton structure, thereby giving the resins b and c photosensitivity, and then giving them developability by the remaining part of the carboxyl groups.
[0043] It should be noted that although a does not have photosensitive properties and cannot participate in photocuring crosslinking, if a portion is appropriately added to the photosensitive resin composition formula below, it can reduce photocuring shrinkage and increase the adhesion between the coating and the substrate. Copolymer a is obtained by copolymerizing (B-1), (B-2) and (B-3), and the copolymer monomer ratio is: B-1 is 10-70% of the total copolymer monomer component of a, preferably 20-60%, B-2 is 5-50% of the total copolymer monomer component of a, preferably 10-40%, and (B-3) is 5-30% of the total copolymer monomer component of a, preferably 10-30%.
[0044] It should be noted that the monoacid (B-1) in the polymerizable monomer in the alkali-soluble resin (B) is acrylic acid, methacrylic acid or a mixture of the two in various ratios.
[0045] It should be emphasized here that the unsaturated polymerizable monomer (B-2) containing an alicyclic skeleton structure having the most important characteristic has a characteristic structure of having a stable alicyclic skeleton structure. Specific examples thereof include: cyclohexyl (meth)acrylate (Evergreen Material EM71), methylcyclohexyl (meth)acrylate, ethylcyclohexyl (meth)acrylate, dicyclohexyl (meth)acrylate, isobornyl (meth)acrylate (Evergreen Material EM90, EM70), adamantyl (meth)acrylate, rosin (meth)acrylate, norbornyl (meth)acrylate, 5-methyl norbornyl (meth)acrylate, 5-ethyl norbornyl (meth)acrylate, Tricyclodecyl (meth)acrylate, dicyclopentyl (meth)acrylate, 1,4-cyclohexane dimethylhydroxy (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate (Changxing Materials EM2051 / EM3052), tricyclodecyloxyethyl (meth)acrylate, etc. Among them, from the perspective of cost economy and synthetic convenience, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, norbornyl (meth)acrylate, rosin (meth)acrylate, tricyclodecyl (meth)acrylate, 2-methyl-2-acrylic acid-2[(2,3,3A,4,7,7A-hexahydro-4,7-methylene-1hydro-indenyl)oxy]ethyl ester are particularly preferred.
[0046] In a preferred embodiment of the present invention, the structural formula of the unsaturated polymerizable monomer (B-2) containing an alicyclic skeleton structure can be listed as follows:
[0047]
[0048] In a more preferred embodiment of the present invention, B-2 is a compound of formula (4) or formula (5).
[0049] It should be noted that the (meth)acrylic acid alkyl ester monomer (B-3) mentioned in the alkali-soluble resin (B) having a carbon chain number of 4 to 20 in the molecule is not particularly limited as long as it has a double bond type unsaturated group and a (meth)acrylic acid ester with a carbon chain number in the range of 4 to 20. Specific examples include: hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, Conventional (meth)acrylate monomers such as lauryl (meth)acrylate, lauryl methyl (meth)acrylate, tridecyl (meth)acrylate, isotridecyl (meth)acrylate, octadecyl (meth)acrylate, or (meth)acrylate monomers containing some special groups, such as trifluoroethyl (meth)acrylate, perfluoroethyl (meth)acrylate, perfluoro-n-propyl (meth)acrylate, perfluoroisopropyl (meth)acrylate, hexafluorobutyl (meth)acrylate, dodecafluoroheptyl (meth)acrylate, tridecafluorooctyl (meth)acrylate, etc.
[0050] As for the unsaturated polymerizable monomer (B-4) containing a single epoxy group and the unsaturated epoxy monomer (B-5) having an alicyclic skeleton used for modification, specific examples include: glycidyl (meth)acrylate, 3,4-epoxycyclohexyl methacrylate, and 3,4-epoxycyclohexyl methyl methacrylate, preferably glycidyl methacrylate and 3,4-epoxycyclohexyl methyl (meth)acrylate.
[0051] In a preferred embodiment of the present invention, the structural formula of the unsaturated epoxy monomer (B-5) having an alicyclic skeleton structure can be listed as follows (8) and (9):
[0052]
[0053] In another preferred embodiment of the present invention, B-5 is preferably a compound of formula (8).
[0054] In a preferred embodiment of the present invention, the ratio of monomers B-2 to B-4 is 0.5-2:1, preferably 1-1.5:1.
[0055] In another preferred embodiment of the present invention, the ratio of monomer B-2 to monomer B-5 is 0.5-2:1, preferably 0.5-1.0:1.
[0056] In another preferred embodiment of the present invention, the monomer having a cyclic structure (B-2 and / or B-5) accounts for 5-50 wt %, preferably 10-40 wt %, and more preferably 10-30 wt % of the total monomers (B-1 to B-5) used to prepare the alkali-soluble resin having a cyclic structure.
[0057] In a preferred embodiment of the present invention, a mixture of resin a and resin b is preferably used as the alkali-soluble resin having a cyclic structure.
[0058] In another preferred embodiment of the present invention, it is preferred to use the resin b as the alkali-soluble resin having a cyclic structure, and more preferably the resin b obtained by using glycidyl methacrylate as the alkali-soluble resin having a cyclic structure.
[0059] The copolymerization reaction of the alkali-soluble resin having a cyclic structure of the present invention () is not particularly limited, and a conventional free radical solution polymerization method can be used. There is no particular restriction on the choice of solvent, and common ethers, esters and hydrocarbon organic solvents can be used. There is no particular restriction on the choice of initiator, and azo and peroxide can be used. There is no particular restriction on the choice of esterification catalyst, and commonly used catalysts (such as tertiary amines, quaternary ammonium salts, triphenylphosphine, etc.) can be used. In addition, it is necessary to add an inhibitor to prevent the polymerization of unsaturated photosensitive groups from causing gel agglomeration.
[0060] The polymerization temperature can be selected in combination with the initiator system.
[0061] The following is a description of the synthesis process of the component B of the photosensitive resin composition of the present invention, namely, the alkali-soluble resin having a cyclic structure:
[0062] The resin is synthesized by various monofunctional unsaturated monomers, which are polymerized by a free radical thermal initiator at a certain temperature in a solvent system, and then modified by a selected unsaturated modified monomer under the catalysis of a catalyst and the protection of an inhibitor, to finally obtain a photosensitive resin composition component B.
[0063] The specific synthesis route is as follows: the selected appropriate solvent is heated to a certain temperature, and various monomers and free radical initiators mixed in a specified proportion are dripped into it. After the dripping is completed according to the designed dripping time, the reaction is carried out at a constant temperature for a corresponding time, and then the free radical initiator is added several times. After the reaction is continued, sampling and characterization are performed to obtain the first part of the photosensitive resin composition component B. Then, at a specific temperature, the selected unsaturated modified monomer, catalyst and inhibitor are completely dissolved, the temperature is raised to a specific temperature to react for a certain time, and after sampling and characterization are qualified, the temperature is lowered to obtain the final photosensitive resin composition component B, and it is stored at room temperature or low temperature. It should be emphasized here that the most critical aspect of the composition component B is the design of the molecular structure, the control of the molecular weight and the acid value. Since polymerization monomers containing other special structures such as alicyclic skeletons are introduced during the polymerization, in order to make the resin have a significantly low D f and low D k When the formula ratio is increased, the polymer side chain after copolymerization contains more alicyclic structures, which will greatly reduce the adhesion between the resin and the substrate. At the same time, due to the alicyclic skeleton structure on the side chain, the solubility of the resin in the developer is reduced, the development time becomes longer or even cannot be developed. For the later ink, the poor development affects the formation of its pattern and causes unqualified effects. Therefore, we need to compound various combination materials, comprehensively consider the various properties of the ink at the beginning of the design, and verify whether the various properties meet the standards through a series of experiments, and finally obtain the best formula composition. In this way, a photosensitive solder mask ink that can be used on 5G communication circuit boards is developed. The most outstanding feature is that it can provide lower dielectric constant and excellent dielectric loss performance to ensure that the cured coating has a lower impact on line transmission.
[0064] On the other hand, the present invention also provides a photosensitive resin composition, which includes:
[0065] (A) an alkali-soluble photocurable resin, in an amount of 40 to 80% by weight, preferably 50 to 70% by weight, based on the total weight of component (A) and component (B);
[0066] (B) the above-mentioned alkali-soluble resin (B) containing a cyclic skeleton structure, which is different from component (A) and has a content of 20-60% by weight, preferably 30-50% by weight, based on the total weight of component (A) and component (B);
[0067] (C) a photopolymerization initiator, in an amount of 0.3-10.0 parts by weight, preferably 0.9-8.0 parts by weight;
[0068] (D) a photosensitive monomer, in an amount of 1-40 parts by weight, preferably 8-30 parts by weight;
[0069] (E) a solvent-type diluent, in an amount of 5-200 parts by weight, preferably 5-100 parts by weight;
[0070] (F) fillers and other additives other than fillers, the content is 30-240 parts by weight, preferably 60-150 parts by weight;
[0071] (G) a thermosetting component, in an amount of 0.6-25 parts by weight, preferably 5-20 parts by weight;
[0072] The amounts of components (B) to (G) are all based on 100 parts by weight of the total weight of components A and B in the photosensitive resin composition.
[0073] In the present invention, the important feature of the photosensitive resin composition component (B) is that it contains an alicyclic skeleton structure, and the content of the unsaturated polymerizable monomers of the alicyclic skeleton structure (i.e., B-2 and / or B-5) in the total polymerizable monomers of the resin (B) is 5-50% by weight, preferably 10-40% by weight, and more preferably 10-30%.
[0074] In one embodiment of the present invention, the alkali-soluble photosensitive resin (A) of the present invention refers to a prepolymer containing both an unsaturated double bond and a carboxyl group in a single molecule, which can be obtained by any of the following methods:
[0075] a. reacting the reaction product of epoxy resin and (meth) acrylic acid with anhydride;
[0076] b. firstly copolymerizing glycidyl (meth) acrylate and a monofunctional unsaturated monomer to obtain an epoxy resin, and then reacting the obtained epoxy resin with acrylic acid, and then reacting with anhydride;
[0077] c. The resin obtained in methods a and b is further reacted with glycidyl (meth)acrylate.
[0078] The alkali-soluble photocurable resin (A) obtained by the above method may be used alone or in the form of a mixture of two or more thereof.
[0079] In a preferred embodiment of the present invention, the solid content acid value of the alkali-soluble photocurable resin (A) of the present invention is 50-150 mgKOH / g, preferably 60-140 mgKOH / g. The amount of alkali-soluble photosensitive resin used is 10-60% by weight, preferably 15-50% by weight, based on the total weight of the resin composition. Since it has more hydroxyl groups produced by grafting reaction and carboxyl groups produced by acid anhydride ring opening, the viscosity of resin A will be within a higher range, which can increase the viscosity adjustment degree of the entire resin composition and keep the solvent E at a higher degree of freedom in coordination. In addition, the design amount of the necessary carboxyl groups and the double bond groups for photocuring crosslinking in the alkali solubility of the resin composition B described later is also not limited.
[0080] Since the alkali-soluble photocurable resin (A) has a high content of carboxyl and double bonds, the overall developability and crosslinking degree of the photosensitive resin composition are improved, so the proportion of some components can be reduced. Therefore, there is a relatively large increase in the polymerizable monomers of the alicyclic skeleton structure in the copolymerized alkali-soluble photosensitive resin (B) containing the alicyclic skeleton structure, and a reduction in the polymerizable monomers that are beneficial to development and the grafting reactive monomers that introduce double bonds.
[0081] In the entire photosensitive resin composition, the combination of the resin part is to make the alkali-soluble photocurable resin (A) tend to have excellent development and photocuring, while the copolymer alkali-soluble photosensitive resin (B) containing an alicyclic skeleton structure tends to have excellent resistance and lower dielectric constant and dielectric loss performance. The final combination ratio makes each performance in the most excellent state.
[0082] In a preferred embodiment of the present invention, the ratio of the amount of the alkali-soluble photocurable resin (A) to the alkali-soluble resin containing a cyclic skeleton (B) is 3 to 1:1, preferably 2 to 1:1, more preferably 1.5 to 1:1.
[0083] In the present invention, the photosensitive resin composition component B is equivalent to an alkali-soluble resin having a cyclic structure. The aforementioned description of the alkali-soluble resin having a cyclic structure is also applicable and need not be repeated here. In the present invention, the photosensitive resin composition component C is a photopolymerization initiator, and commonly used photoinitiators include the following compounds: acetophenones such as acetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, and 1,1-dichloroacetophenone; benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and other benzoin alkyl ethers; 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinoacetone-1,2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butane-1-one, N,N-dimethylaminoacetophenone, and other aminoacetophenones; 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthracene quinone, 1-chloroanthraquinone and other anthraquinones; 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, 2-chlorothioxanthone, 2,4-diisopropylthioxanthone and other thioxanthones; acetophenone dimethyl ketal, benzyl dimethyl ketal and other ketals; organic peroxides such as benzoyl peroxide and isopropyl peroxide; riboflavin tetrabutyl ester, 2-thiobenzimidazole, 2-thiobenzoxazole, 2-thiobenzothiazole and other thiol compounds; 2,4,6-tri-s-triazine, 2,2,2-tribromoethanol, tribromomethylphenyl ketone and other organic halides; benzophenone, 4,4'-bis-diethylaminobenzophenone and other benzophenones or thioxanthones; 2,4,6-tribenzoyldiphenylphosphine oxide. The above-mentioned photopolymerization initiators can be used alone or in combination. Regarding the usage amount, based on 100 parts by weight of the total weight of the photosensitive resin composition components A and B, the content of the photoinitiator C is 0.5-12 parts by weight, preferably 1.5-8 parts by weight.
[0084] In the present invention, the photosensitive monomer of the photosensitive resin composition component D can be listed as: hydroxyl-containing (meth)acrylates such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, pentaerythritol tri(meth)acrylate, and dipentaerythritol penta(meth)acrylate; monofunctional (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, and lauryl (meth)acrylate; difunctional (meth)acrylates such as 1,6-hexanediol di(meth)acrylate, dipropylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, and neopentyl glycol diethoxy / propoxy di(meth)acrylate; multifunctional (meth)acrylates such as trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and dipentaerythritol hexa(meth)acrylate, etc.
[0085] The amount used is based on the total weight of the photosensitive resin composition components A and B as 100 parts by weight, and the content of the photosensitive monomer D is 1-40 parts by weight, preferably 8-30 parts by weight. When the content is too high, the film layer will be soft, and the coating will not be dried after pre-baking, or its softening point will be low at room temperature and will be soft and sticky. At this time, a layer of film pattern will be covered on the ink coating during the exposure process stage, and in order to ensure the efficiency of photocuring, the ink coating and the film will be more closely fitted by vacuum extrusion, which will cause the ink coating to stick to the film and there will be film marks. However, when the content is too low, the film layer sensitivity will be too low, which is not conducive to the photosensitivity.
[0086] In the present invention, the solvent diluent of the photosensitive resin composition component E can be listed as: ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono-n-propyl ether, ethylene glycol mono-n-butyl ether, diethylene glycol monomethyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol dimethyl ether, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol mono-n-butyl ether, tripropylene glycol monomethyl ether, and tripropylene glycol monoethyl ether; ethylene glycol methyl ether acetate , ethylene glycol ethyl ether acetate, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, dipropylene glycol monomethyl ether acetate, dipropylene glycol monoethyl ether acetate, dipropylene glycol monobutyl ether acetate and other esters; ketones such as methyl ethyl ketone, cyclohexanone, heptanone; aromatic hydrocarbons such as toluene and xylene; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; petroleum solvents such as petroleum ether and naphtha, etc.
[0087] The solvent selection requirement of the present invention is generally an organic solvent with a boiling point of 100-250° C., preferably 130-230° C. The content is selected to be 5-200 parts by weight, preferably 5-100 parts by weight, based on the total weight of the photosensitive resin composition components A and B as 100 parts by weight. The above-mentioned solvents can be used alone or in combination.
[0088] In the present invention, the photosensitive resin composition further contains pigments, fillers and other additives F.
[0089] In the present invention, the color filler comprises pigment and inorganic filler.
[0090] There is no particular limitation on the inorganic filler, which may be exemplified by barium sulfate, talc, quartz powder, mica powder, silica powder, clay, magnesium carbonate, calcium carbonate, alumina powder, kaolin, silicon dioxide, etc. These inorganic fillers may be used alone or in the form of a mixture thereof. The formula ratio is based on 100 parts by weight of the total weight of the photosensitive resin composition components A and B, and the amount of the inorganic filler added is 30-210 parts by weight, preferably 60-120 parts by weight.
[0091] There is no particular limitation on the pigments, which may be phthalocyanine green, phthalocyanine blue, titanium dioxide, carbon black, lithopone, permanent violet, permanent yellow, and ultramarine. The above pigments may be used alone or in combination. The amount of the pigment is 0-3 parts by weight, preferably 0.5-1 part by weight, based on 100 parts by weight of the total of the photosensitive resin composition components A and B. The specific situation is based on the toning ratio, but it is not limited thereto.
[0092] The auxiliary agent may be an epoxy resin curing accelerator, a photoinitiator auxiliary agent, a defoamer, a leveling agent, a thixotropic tackifier, etc., and all conventional compounds in the art may be used. The formula ratio is based on the total weight of the photosensitive resin composition components A and B being 100 parts by weight, and the amount of the auxiliary agent added is 0-50 parts by weight, preferably 1-25 parts by weight, but not limited thereto.
[0093] In one embodiment of the present invention, the defoamer can be silicone-based, acrylate-based, or a mixture of the two types of defoamers, including but not limited to the common ones such as KS-66 from Shin-Etsu Co., Ltd. of Japan; defoamers from TEGO Co., Ltd. of Germany: Foamex N, Foamex 815N, Foamex 825, Foamex 840, Foamex 842; defoamers from Deqian Hemmings: DEUCHEM 3200, DEUCHEM 3500, DEUCHEM 5300, DEUCHEM 5400, DEUCHEM 5600, DEUCHEM6500, DEUCHEM 6800; DEUCHEM 6600, etc.; acrylate defoamers from BYK Co., Ltd. of Germany: BYK-051, BYK-052, BYK-053, BYK-057, etc. Based on 100 parts by weight of the total solid content of the photosensitive resin composition components (A) and (B), the content of the defoaming agent may be 0.05-20 parts by weight, preferably 0.1-10 parts by weight, and more preferably 0.5-3 parts by weight.
[0094] In one embodiment of the present invention, the leveling agent may be a leveling agent conventionally used in the art, including but not limited to BYK-354, BYK-306, BYK-399, etc., or mixtures thereof, and other leveling agents may also be used without special restrictions. Based on 100 parts by weight of the total weight of the solid components of the photosensitive resin composition components (A) and (B), the content of the leveling agent may be 0.05-40 parts by weight, preferably 0.1-20 parts by weight, and more preferably 0.2-5 parts by weight.
[0095] In summary, when preparing the resin composition, the various components mentioned above can be added according to the formula ratio and then uniformly mixed.
[0096] In the present invention, the thermosetting component G of the photosensitive resin composition refers to an epoxy compound (epoxy resin) containing two or more epoxy groups in one molecule, which can be exemplified as:
[0097] Bisphenol A epoxy resin and its hydrogenated products (E20, E42, E44, E51, E54, etc.), bisphenol F epoxy resin (F48, F51), bisphenol S epoxy resin, novolac epoxy resin, biphenol epoxy resin, dixylenol epoxy resin, trisphenol methane epoxy resin, N-glycidyl epoxy resin, 2,6-xylenol dimer diglycidyl ether, aliphatic epoxy resin, xylene epoxy resin.
[0098] The epoxy compound can be used alone or in the form of a mixture thereof. The total weight of the photosensitive resin composition components A and B is 100 parts by weight, and the content of the thermosetting component G is 1-40 parts by weight, preferably 8-30 parts by weight. When the content of the thermosetting component is too low, the coating resistance after film formation will be insufficient, while when the content is too high, the problem of unclean development will occur.
[0099] Example
[0100] Below, the present invention will be described in more detail by the following synthesis examples and embodiments. However, these embodiments are only used to illustrate and explain the present invention, but not to limit the present invention, and the scope of the present invention is not limited thereto.
[0101] According to the following synthesis example, an alkali-soluble photocurable resin (A) was prepared:
[0102] 203g of o-cresol epoxy resin (SQPN-704M purchased from Shandong Shengquan New Materials Co., Ltd., with an epoxy equivalent of 210), 0.5g of hydroquinone (purchased from Mitsui Chemicals of Japan), 180g of diethylene glycol ethyl ether acetate (purchased from Tianyin Chemical), and 60g of tetramethylbenzene (purchased from Hualun Chemical) were added to a three-necked flask and mixed and stirred. The temperature was raised to 100-110°C and stirred and dissolved for 1 hour. After ensuring complete dissolution, the temperature was lowered to 90°C, and a mixed solution of 72g of acrylic acid (purchased from Satellite Petrochemical) and 1g of triphenylphosphine (purchased from Bisheng Chemical) was added dropwise. The addition time was maintained at 3 hours (with a deviation of no more than 10 minutes). The temperature was controlled at 90-100°C during the addition process. After the addition was completed, the temperature was raised to a constant temperature range of 105-110°C for reaction for 12 hours, and then a sample was taken to determine the resin acid value, which was less than 10mgKOH / g
[0103] The material temperature was cooled to 90°C by titration with KOH standard solution, 60 g of tetrahydrophthalic anhydride (purchased from Puyang Huicheng) was added, and the reaction was kept at 90°C for 3 hours to obtain a light yellow resin A with a viscosity of 350 dPa·s, a solid content of 58%, a weight average molecular weight (Mw) of 5000 (determined by GPC gel permeation chromatography) and a solid acid value of 80 mgKOH / g.
[0104] According to the following synthesis examples, an alkali-soluble photosensitive resin (B) containing an alicyclic structure was prepared: Synthesis Example 1
[0105] Assemble stirring blades, constant pressure dropping funnel, thermometer, condensing reflux tube and vent pipe on a five-necked flask. After assembling the inspection device and firmly sealing it, add 160g of diethylene glycol ethyl ether acetate, pass nitrogen, set the oil bath temperature to 80°C and start stirring. After the material temperature reaches 80°C, start dripping a mixture consisting of 120g of diethylene glycol ethyl ether acetate, 38.7g of methacrylic acid, 22g of cyclohexyl methacrylate, 79.2g of methyl methacrylate and 1.5g of azobisisobutyronitrile (purchased from Nantong Runfeng). The dripping time is 2 hours, and the temperature is kept at 80°C during the dripping process. After the dripping is completed, the polymerization reaction is further stirred at 80°C for 5 hours to obtain an alkali-soluble resin solution with a weight average molecular weight of 17000 and a solid acid value of 178KOHmg / g.
[0106] Synthesis example 2
[0107] In the solution of Synthesis Example 1, 20 g of glycidyl methacrylate, 0.5 g of p-hydroxyanisole and 0.5 g of triphenylphosphine were added, and the mixture was stirred and heated at 110° C. for 8-10 hours to obtain an alkali-soluble unsaturated resin solution having a weight average molecular weight of 25,000 and a solid acid value of 104 KOHmg / g. The viscosity thereof was measured to be 80 dPa·s (25° C.).
[0108] The same process was repeated multiple times, and the results were all a weight average molecular weight of 25,000 and good reproducibility of molecular weight distribution, acid value and viscosity.
[0109] Synthesis example 3
[0110] In the solution of Synthesis Example 1, 28 g of 3,4-epoxycyclohexylmethyl (meth)acrylate was added, and 10 g of diethylene glycol ethyl ether acetate, 0.5 g of p-hydroxyanisole, and 0.5 g of triphenylphosphine were added, and stirred and heated at 110° C. for 8-10 hours to obtain an alkali-soluble unsaturated resin solution with a weight average molecular weight of 22,000 and a solid acid value of 110 KOHmg / g. The viscosity was measured to be 60 dPa·s (25° C.).
[0111] The same reaction process was repeated multiple times, and the results were all a weight average molecular weight of 22,000 and good reproducibility of molecular weight distribution, acid value and viscosity.
[0112] Synthesis example 4
[0113] Other conditions remain unchanged, only 22g of cyclohexyl methacrylate in Synthesis Example 1 is replaced with 22g of isobornyl methacrylate, and the same polymerization process is used to obtain an alkali-soluble resin solution with a weight average molecular weight of 18,000 and a solid acid value of 178KOHmg / g. The same reaction is repeated many times, and the molecular weight, molecular weight distribution and acid value have good reproducibility.
[0114] Synthesis example 5
[0115] In the solution of Synthesis Example 4, 20 g of glycidyl methacrylate, 0.5 g of p-hydroxyanisole and 0.5 g of triphenylphosphine were added, and the mixture was stirred and heated at 110°C for 8-10 hours to obtain an alkali-soluble unsaturated resin solution with a weight average molecular weight of 27,000 and a solid acid value of 104 KOHmg / g. The viscosity thereof was measured to be 90 dPa·s (25°C). The same reaction was carried out for many times, and the molecular weight distribution, acid value and viscosity had good reproducibility.
[0116] Synthesis example 6
[0117] In the solution of Synthesis Example 4, 28 g of 3,4-epoxycyclohexyl methyl (meth) acrylate was added, and 10 g of diethylene glycol ethyl ether acetate, 0.5 g of p-hydroxyanisole, and 0.5 g of triphenylphosphine were added, and stirred and heated at 110° C. for 8-10 hours to obtain an alkali-soluble unsaturated resin solution with a weight average molecular weight of 24,000 and a solid acid value of 110 KOHmg / g. The viscosity was measured to be 70 dPa·s (25° C.). The same reaction was carried out many times, and the molecular weight distribution, acid value and viscosity had good reproducibility.
[0118] Synthesis Comparative Example 1
[0119] Other conditions remain unchanged, only 22g of cyclohexyl methacrylate in Synthesis Example 1 is replaced with 22g of n-butyl methacrylate, and the same polymerization process is used to obtain an alkali-soluble resin solution with a weight average molecular weight of 17000 and a solid acid value of 178KOHmg / g. The same reaction is repeated many times, and the molecular weight, molecular weight distribution and acid value have good reproducibility.
[0120] Synthesis Comparative Example 2
[0121] Other conditions remain unchanged, only 22g of cyclohexyl methacrylate in Synthesis Example 1 is replaced with 22g of isooctyl methacrylate, and the same polymerization process is used to obtain an alkali-soluble resin solution with a weight average molecular weight of 17000 and a solid acid value of 178KOHmg / g. The same reaction is repeated many times, and the molecular weight, molecular weight distribution and acid value have good reproducibility.
[0122] Synthesis Comparative Example 3
[0123] In the solution of Comparative Example 1, 20 g of glycidyl methacrylate, 0.5 g of p-hydroxyanisole and 0.5 g of triphenylphosphine were added, and the mixture was stirred and heated at 110°C for 8-10 hours to obtain an alkali-soluble unsaturated resin solution with a weight average molecular weight of 25,000 and a solid acid value of 104 KOHmg / g. The viscosity thereof was measured to be 50 dPa·s (25°C). The same reaction was carried out for many times, and the molecular weight distribution, acid value and viscosity had good reproducibility.
[0124] Comparative Synthesis Example 4
[0125] In the solution of Comparative Example 2, 20 g of glycidyl methacrylate, 0.5 g of p-hydroxyanisole and 0.5 g of triphenylphosphine were added, and the mixture was stirred and heated at 110°C for 8-10 hours to obtain an alkali-soluble unsaturated resin solution with a weight average molecular weight of 25,000 and a solid acid value of 104 KOHmg / g. The viscosity thereof was measured to be 50 dPa·s (25°C). The same reaction was carried out for many times, and the molecular weight distribution, acid value and viscosity had good reproducibility.
[0126] The present invention mixes the components A to G of the photosensitive resin composition (component G of the liquid composition is added last), and the main difference of the present invention lies in the selection and distinction of the component B of the photosensitive resin composition. The components A to G are completely and evenly mixed with a disperser and a grinder (three-roller mill, etc.) (component G of the liquid composition can be added and evenly dispersed before printing construction), and the photosensitive resin composition with low dielectric constant and low dielectric loss of the present invention can be obtained.
[0127] The photosensitive resin composition of the present invention obtained above is coated on the laminate covered with copper foil, and the coating thickness is 10 to 100 μm. The coating is applied by screen printing, electrostatic spraying, roller coating and coating. After the resin composition is applied, it is placed in a closed oven at a temperature of 50 to 100°C and pre-baked for 10 to 100 minutes to make the coating surface non-sticky. After cooling to 25°C, a specific negative film that is partially light-shielding and partially light-transmitting is placed on the coating. After vacuuming under negative pressure, the surface is exposed with a UV exposure machine (the exposure energy is selected to be 10 to 1000 mJ / cm 2The exposure equipment includes a conventional UV exposure machine, an LDI exposure machine, etc.). After the exposure is completed, the developer is used for development, and the coating of the non-exposed area is dissolved and washed away to obtain the desired pattern. The developer is generally a 1 to 5% sodium carbonate aqueous solution, but is not limited to this alkali solution (it can also be potassium carbonate, organic alkali, etc.).
[0128] After the development is completed, a preliminary inspection is carried out, and then it is placed in an oven at a temperature of 120 to 180°C for 30 to 90 minutes, or cured with a UV energy machine at a constant temperature to obtain an ideal solder mask coating. In the subsequent electronic circuit board production process, electronic components are soldered on the bare circuit board without solder mask coating.
[0129] The present invention is not limited to a photosensitive resin composition with low dielectric constant and low dielectric loss, but also includes a solder resist circuit board formed after coating the photosensitive resin composition.
[0130] The present invention selects the synthesis example and the comparative synthesis example of the photosensitive resin composition B component and mixes it with the remaining components to prepare a photosensitive resin composition with low dielectric constant and low dielectric loss. Examples 1 to 6 and Comparative Examples 1 to 4 (the formulations of the embodiments and comparative examples of the resin composition are shown in Table 1)
[0131] In Examples 1 to 6 and Comparative Examples 1 to 4, components A to F were mixed uniformly according to the resin composition formulation shown in Table 1 below, dispersed for 30 minutes using a high-speed stirrer (Qinkai U400), and then ground using a three-roll grinder (Chiller S65) to a particle size of less than 20 μm (scraper fineness meter Jinfulun QXP100ISO) to obtain a portion of the resin composition, which was mixed with the dissolved and ground composition G into a liquid state before use, stirred uniformly, and then used.
[0132]
[0133]
[0134] Component F MEHQ, p-hydroxyanisole, purchased from Nantong Runfeng Petrochemical Co., Ltd. Component F phthalocyanine green, purchased from BASF's L9361
[0135] Component F melamine, purchased from Kunshan Rongzhiyu Fine Chemical Co., Ltd.
[0136] Component F silica, spherical silica purchased from Jiangsu Lianrui New Materials
[0137] Component F defoamer, purchased from Shin-Etsu Chemical KS66
[0138] Component F leveling agent, BYK-300 purchased from BYK, Germany
[0139] Component G704M, o-cresol epoxy resin, purchased from Shandong Shengquan Company's 704M
[0140] Component G TGIC, triglycidyl isocyanurate, purchased from Hengqiao Industrial Co., Ltd.
[0141] The measurement and judgment criteria of the photosensitive resin composition component B are as follows:
[0142] Weight average molecular weight of component B of the photosensitive resin composition: GPC, polystyrene as standard sample conversion integral, tetrahydrofuran as mobile phase, equipment is Waters1515, Waters2414, chromatographic column is WatersStyragel HR3, HR4, HR5 (Waters Corporation, USA)
[0143] Acid value of component B of the photosensitive resin composition: titration with standard potassium hydroxide aqueous solution (1 mol / L), phenolphthalein ethanol solution as indicator
[0144] Viscosity of the photosensitive resin composition component B: JULABO200F constant temperature water bath, TOKI viscometer TV-35
[0145] The solid content of the photosensitive resin composition component B is determined by the method for determining the solid content of coatings in accordance with GB1725-1979.
[0146]
[0147] The construction method adopted by the present invention is screen printing, but the construction properties described in the present invention are not limited to screen printing properties, but also include all the above construction properties, which are only verified by the screen printing method.
[0148] The photosensitive resin compositions prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were prepared with open oil water (DBE: tetramethylbenzene = 6:4) to a viscosity of 50 dPa·s, and the same mass (about 50 g) was weighed, and then the photosensitive resin compositions prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were printed on a clean and dry copper foil circuit board by 40T screen printing, and the construction properties were evaluated according to the following standards:
[0149] ○: The coating has no screen printing, good leveling, no bubbles, wrinkles, shrinkage and other undesirable phenomena
[0150] ◇: The coating has screen printing, good leveling, and a small amount of bubbles, wrinkles, shrinkage and other undesirable phenomena
[0151] △: The coating has screen printing, good leveling, and a small amount of bubbles, wrinkles, shrinkage and other undesirable phenomena
[0152] ×: The coating has screen printing, poor leveling, a large number of bubbles, wrinkles, edge shrinkage and other undesirable phenomena.
[0153] Test Item 2: Aging Stability
[0154] The photosensitive resin compositions prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were weighed in the same mass (about 200 g) and added into a 300 ml sealed can, sealed and placed in a 75° C. oven for 1 hour, and then taken out and cooled to room temperature in a sealed state to test the viscosity of each experimental group. The storage stability was evaluated using the following criteria.
[0155] ○: Viscosity increase ≤10%
[0156] ◇: Viscosity increases by 10 to 30%;
[0157] △: Viscosity increased by 30 to 50%
[0158] ×: Viscosity increase > 50%
[0159] Test Item 3: Development
[0160] Prepare the sample plate using the method of test item 1 and place it in a hot air circulation oven at 75°C for 40 / 50 / 60 minutes. After the drying time is reached, take it out and place it in a dark environment to cool to room temperature, then transfer it to a 30°C, 1% Na 2 CO 3 The developer was placed on a developer with a spraying time of 60 seconds and a spraying pressure of 0.1 MPa (under a yellow light background throughout the process). After development, the coating residue was observed and the developability was evaluated according to the following standards.
[0161] ○: No coating residue on the board surface after 40 / 50 / 60 minutes
[0162] ◇: No coating residue on the board surface after 40 / 50 minutes, but some residue after 60 minutes
[0163] △: No coating residue on the board surface after 40 minutes, but some residue on the board surface after 50 / 60 minutes
[0164] ×: The coating on the board remains after 40 / 50 / 60 minutes
[0165] Test Item 4: Photosensitivity (level)
[0166] Prepare a sample plate using the method of test item 1, and place it in a hot air circulation oven at 75°C for 40 minutes. After the drying time is reached, take it out and place it in a dark environment to cool to room temperature. Then use a UV exposure machine equipped with a 7kW metal halide lamp (AMBA7000) to expose the coating through a 21-step exposure ruler (Stouffer exposure ruler, model T2115) (exposure energy is set to 300mJ / cm2, ambient temperature is 25°C), and then transfer it to a 30°C, 1% Na 2 CO3 The developer was placed on a yellow light background with a spraying time of 60 seconds and a spraying pressure of 0.1 MPa. After completion, the Stouffer value of each experimental group was recorded.
[0167] Test Item 5: Adhesion
[0168] Prepare a sample plate using the method of test item 1, and place it in a hot air circulation oven at 75°C for 40 minutes. After the drying time is reached, take it out and place it in a dark environment to cool to room temperature, then use a UV exposure machine equipped with a 7kW metal halide lamp (AMBA7000) to expose the entire plate (set the exposure energy to 500mJ / cm2, the ambient temperature to 25°C), and then transfer it to a 30°C, 1% Na 2 CO 3 The coating was placed in a developer with a spraying time of 60 seconds and a spraying pressure of 0.1 MPa (under a yellow light background). Then it was placed in a hot air circulation oven at 150°C for 60 minutes. After cooling to room temperature, the adhesion of each experimental group of coatings was tested using the 100-grid method (GB9286-98 100-grid test standard) and the adhesion was evaluated according to the following standards.
[0169] ○: ≥4B Small pieces fall off at the intersection of the lines, and the falling pieces account for less than 5% of the total area
[0170] ◇: Small pieces fall off at the edges and intersections of the 4B to 3B lines, and the falling pieces account for less than 5 to 15% of the total area
[0171] △: Large pieces fall off at the edges and intersections of the 3B to 2B lines, and the shedding accounts for less than 15 to 35% of the total area
[0172] ×: ≤2B Large pieces fall off at the edges and intersections of the line, and the falling pieces account for less than ≥35% of the total area
[0173] Test Item 6: Hardness
[0174] In a clean and undamaged area of the coating sample after testing item 5, use a 6H pencil (Mitsubishi brand), sharpen the lead into a cylindrical shape and grind it flat on 400-grit sandpaper, then install it on a special pencil hardness tester (the load applied to the tip of the pencil is 1 kg, and the pencil maintains an angle of 45° with the horizontal plane). Push the pencil forward horizontally to slide about 5 mm long, draw a total of 5 lines, and then use an eraser to wipe off the pencil marks. Evaluate the hardness according to the following evaluation criteria.
[0175] ○: No scratches
[0176] ◇: Slight scratches
[0177] △: Heavy scratches
[0178] ×: Exposed copper
[0179] Test Item 7: Heat Resistance
[0180] Prepare a non-destructive test sample in the same way as test item 5, apply rosin flux on the sample, and then immerse it in a 280°C tin furnace tank for 3 times (staying for 10 seconds each time), wash it with propylene glycol methyl ether acetate and dry it, and then use 3M tape to perform a sticking test. Evaluate heat resistance according to the following standards.
[0181] ○: No blistering, sticking or peeling of the resin composition coating
[0182] ◇: The resin composition coating has a small amount of bubbling and sticking, but no falling off
[0183] △: The resin composition coating has a small amount of bubbling, sticking, and falling off
[0184] ×: The resin composition coating completely peeled off
[0185] Test Item 8: Chemical Resistance
[0186] Prepare a non-destructive test sample in the same way as test item 5, immerse it in propylene glycol methyl ether acetate for 30 minutes, then immerse it in anhydrous alcohol (purity ≥ 99.5%) for 30 minutes, then take it out, wash it with water and dry it. Then use 3M tape to perform the adhesion test, and evaluate the chemical resistance according to the following standards.
[0187] ○: No blistering, sticking or peeling of the resin composition coating
[0188] ◇: The resin composition coating has a small amount of bubbling and sticking, but no falling off
[0189] △: The resin composition coating has a small amount of bubbling, sticking, and falling off
[0190] ×: The resin composition coating completely peeled off
[0191] Test Item 9: Dielectric Strength
[0192] A 10cm*10cm copper substrate with a thickness of 35 to 40 mm was selected, and the oxide layer on the copper surface was pickled with a grinding machine. After needle brush polishing, water washing, air drying and baking, the surface of the copper substrate was evenly wrapped with tin foil, spread horizontally without wrinkles (fixed with a high temperature resistant tape), and then the photosensitive resin composition prepared in Examples 1 to 6 and Comparative Examples 1 to 4 was printed on the treated board with a 40T screen. Then it was placed in a drying oven with a hot air circulation of 75°C and baked for 40 minutes. It was taken out and cooled to room temperature, and then the screen printing and drying (3-4 times) were repeated to obtain a copper plate with a coating thickness of the photosensitive resin composition ≤ 80 mm, and the entire plate was exposed with a UV exposure machine (AMBA7000) equipped with a 7kW metal halide lamp (the exposure energy was set to 500mJ / cm 2 , ambient temperature 25°C) and then transferred to 30°C, 1% Na 2 CO 3 The aqueous solution was sprayed on a developer with a spraying time of 60 seconds and a spraying pressure of 0.1 MPa (under yellow light background throughout the process). Then it was placed in a hot air circulation oven at 150°C and baked for 60 minutes. After cooling to room temperature, the photosensitive resin composition coating was peeled off from the tin foil with tweezers and cut into block samples of 50*50mm and thickness ≤80mm.
[0193] The samples prepared as above were subjected to RF testing and measurement at room temperature using a vector network analyzer (Rohde & Schwarz ZNA50 10 MHz to 50 GHz) at a frequency of 10 GHz using the resonant cavity method to obtain the values of the dielectric constants of Examples 1 to 6 and Comparative Examples 1 to 4 (results are shown in Table 3), and the results were compared and evaluated.
[0194] Test Item 10: Dielectric Loss
[0195] The preparation and testing methods of this project are the same as those of test project 9, and the values of the dielectric loss factors of embodiments to 6 and comparative examples 1 to 4 are obtained (results are shown in Table 3), and the results are compared and evaluated.
[0196]
[0197] In terms of performance, it has the characteristics of low dielectric constant (Dk) and significantly reduced dielectric loss (E), which effectively solves the problem of signal loss and obstruction of the photosensitive resin composition coating in high-frequency environments on 5G communication substrates.
Claims
1. A photosensitive resin composition comprising: (A) an alkali-soluble photocurable resin, which is a prepolymer containing both an unsaturated double bond and a carboxyl group in a single molecule, and the content thereof is 40-80% by weight, based on the total weight of component (A) and component (B); (B) an alkali-soluble resin having a cyclic structure, which is different from component (A) and is present in an amount of 20 to 60% by weight, based on the total weight of component (A) and component (B); (C) a photopolymerization initiator, in an amount of 0.3-10 parts by weight; (D) a photosensitive monomer, in an amount of 1 to 40 parts by weight; (E) a solvent-type diluent in an amount of 5 to 200 parts by weight; (F) pigments and fillers and other additives other than pigments and fillers, the content is 30-240 parts by weight; (G) a thermosetting component, in an amount of 0.6-25 parts by weight; The amounts of components (C) to (G) are based on 100 parts by weight of the total weight of components (A) and (B) in the photosensitive resin composition; The alkali-soluble resin (B) having a cyclic structure is one or a combination of the following resins a, b and c: Resin a. is a copolymer obtained by copolymerizing an unsaturated monobasic acid (B-1), a polymerizable monomer containing a cyclic structure (B-2) and an alkyl (meth)acrylate monomer (B-3) under a free radical initiation system, wherein the alkyl group in the monomer (B-3) is a chain alkyl group having 4 to 20 carbon atoms; Resin b is a resin obtained by reacting the resin a and an unsaturated polymerizable monomer having an epoxy group (B-4); Resin c is a resin obtained by reacting the resin a and an unsaturated epoxy monomer having an alicyclic skeleton (B-5); The alkali-soluble resin (B) having a cyclic structure contains an alicyclic skeleton structure, and the content of the monomer (B-2) in the total polymerized monomers of the alkali-soluble resin having a cyclic structure is 10-30% by weight.
2. The composition according to claim 1, comprising: (A) an alkali-soluble photocurable resin, which is a prepolymer containing both an unsaturated double bond and a carboxyl group in a single molecule, and its content is 50-70% by weight, based on the total weight of component (A) and component (B); (B) an alkali-soluble resin having a cyclic structure, which is different from component (A) and is contained in an amount of 30 to 50% by weight, based on the total weight of component (A) and component (B); (C) a photopolymerization initiator, in an amount of 0.9 to 8 parts by weight; (D) a photosensitive monomer, in an amount of 8 to 30 parts by weight; (E) a solvent-type diluent, in an amount of 5 to 100 parts by weight; (F) pigments and fillers and other additives other than pigments and fillers, the content is 60-150 parts by weight; (G) a thermosetting component, in an amount of 5 to 20 parts by weight; The amounts of components (C) to (G) are based on 100 parts by weight of the total weight of components (A) and (B) in the photosensitive resin composition.
3. The composition according to claim 1 or 2, wherein the unsaturated monoacid (B-1) is (meth)acrylic acid or acrylic acid or a mixture of the two in any proportion; and the cyclic structure of the polymerizable monomer (B-2) is an alicyclic skeleton structure. The composition according to claim 3 , wherein the unsaturated monobasic acid (B-1) is (meth)acrylic acid.
5. The composition according to claim 1 or 2, wherein the polymerizable monomer (B-2) is selected from compounds having the following structures: 6 . The composition according to claim 5 , wherein the polymerizable monomer (B-2) is selected from compounds having a structure of formula (4) or formula (5).
7. The composition according to claim 1 or 2, wherein the monomer (B-4) is an unsaturated epoxy monomer or a prepolymer thereof.
8. The composition according to claim 7, wherein the unsaturated epoxy monomer is glycidyl methacrylate.
9. The composition according to claim 1 or 2, wherein the unsaturated epoxy monomer (B-5) having an alicyclic skeleton is a compound of formula (8) or formula (9): 10 . The composition according to claim 9 , wherein the unsaturated epoxy monomer (B-5) having an alicyclic skeleton is a compound of formula (8).
11. The composition according to claim 1 or 2, wherein the amounts of monomers (B-1), (B-2) and (B-3) used to prepare the resin a are: (B-1) 10-70 wt %; (B-2) 10-30 wt %; (B-3) 5-30 wt %, all based on the total amount of monomers used to prepare the resin a as 100 wt %.
12. The composition according to claim 11, wherein the amounts of monomers (B-1), (B-2) and (B-3) used to prepare the resin a are: (B-1) 20-60 wt %; (B-2) 10-30 wt %; (B-3) 10-30 wt %, all based on the total amount of monomers used to prepare the resin a as 100 wt %.
13. The composition according to claim 1 or 2, wherein the content of the monomer (B-5) in the total polymerized monomers of the alkali-soluble resin having a cyclic structure is 5 to 50% by weight. 14 . The composition according to claim 13 , wherein the content of the monomer (B-5) in the total polymerized monomers of the alkali-soluble resin having a cyclic structure is 10 to 40% by weight. 15 . The composition according to claim 14 , wherein the content of the monomer (B-5) in the total polymerized monomers of the alkali-soluble resin having a cyclic structure is 10 to 30% by weight.
16. The composition according to claim 1 or 2, wherein the solid content acid value of the alkali-soluble photocurable resin (A) is 50 to 150 mgKOH / g. 17 . The composition according to claim 16 , wherein the solid content acid value of the alkali-soluble photocurable resin (A) is 60 to 140 mgKOH / g.
18. A circuit board, characterized in that: It comprises a cured coating formed from the composition according to any one of claims 1 to 17.
19. Use of the circuit board according to claim 18 in manufacturing 5G communication equipment.
Citation Information
Patent Citations
Composition Used For Formation Of Transparent Insulation Membrane
CN104102091A
Copolymer, anti-rust coating composition containing copolymer, dispersant containing copolymer, and anti-corrosion resin containing copolymer
CN114930251A